THE PLACE OF CUSTOMS LAW IN THE STRUCTURE OF THE LEGAL SYSTEM: SOME PROPOSALS FOR DEFINITION - Riabchenko, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to substantiate the scientific approach to determining the place of customs and legal regulation in the structure of legal order. Research methods: systematic approach to the formation of the approach to the definition of customs law in the law system structure; systematic analysis together with the classification method was used to determine the priority for the study of the problem of customs legal regulation, as well as the systematization of subjects of customs legal relations; comparative legal approach for disclosing the correlation of customs legal relations related to the implementation of the state customs affairs and administrative and legal relations; the method of legal modelling to determine the object, forms and methods of customs legal regulation. Results: substantiation of the need to identify the risks and dangers that affect the state of security of foreign economic activities and customs legal regulation; definition of the object of customs legal regulation as a polystructural object; proving the expediency of joining the approach, according to which the customs law is considered as a sub-branch of administrative law; highlighting of the subjective component of customs law. Discussion: the necessity of disclosing the essence and content of the customs legal regulation in the conditions of the high level of dangers concerning the risks of their occurrence is argued, which actualizes the issue of establishing and applying appropriate measures and means of customs legal regulation and the priority of its security component. We propose to define customs law as a same-name complex branch of law based on the provisions of the relevant sub-branch of administrative law. This approach takes into account the ordering, mainly organizational nature of customs legal regulation, the administrative and legal nature of customs-tort relations and relations on guaranteeing the legality of activities of the customs authorities, the introduction into the structure of the system of customs legal relations of those related to law enforcement activities, as well as the relationship with constitutional and legal, financial and legal, civil, economic and legal and other relations.